Establishing consensus on the implementation of Anticoagulation Stewardship Program with cardiologists in Pakistan: A Delphi study - Wajiha Razzaq; Muhammad Atif; Kanza Arshad; Imran Masood (PLoS ONE, 2025)
Background The Anticoagulation Stewardship Program (ASP) improves clinical outcomes, promotes patient safety, and supports healthcare systems in delivering high-quality, evidence-based anticoagulation management. This study aimed to develop a consensus among cardiologists about the implementation of the ASP Program in Pakistan. Methods A three-round Delphi study was conducted utilizing an online questionnaire. In Round 1, cardiologists (Delphi panel experts) reported their consensus with the items in the questionnaire using a 3-point Likert scale. The selection of items for Round 2 was based on acceptance by ≥66.6% of the cardiologists and the agreement of the scientific committee. In Round 2, the panelists assessed those items that failed to gain consensus in Round 1. In Round 3, a face-to-face meeting was conducted among the scientific committee to evaluate the items that failed to gain expert agreement in Round 2 to form the final consensus document. Descriptive statistics was used to present the data. Results A total of 90 cardiologists from 30 hospitals were invited to participate in the study. Of these, 75 agreed to participate in Round 1 of the study (83% response rate). 68 cardiologists completed the survey in Round 2. Initially, 33 items from four domains were evaluated by the Delphi experts in Round 1. 18 items reached consensus in Round 1, 4 items reached consensus in Round 2, and 2 items reached consensus in Round 3. The final consensus document comprised 24 items. The study showed absolute consensus among national cardiologists regarding the implementation of ASP in Pakistan. A considerable agreement was achieved regarding essential components needed to strengthen ASP for anticoagulation management in the cardiology departments. Conclusion This study emphasized the need for educational sessions for patients and healthcare professionals, collaboration with healthcare authorities, and allocation of financial resources for ASP. This study also identified consensus among cardiologists on the perceived benefits of ASP for patients and the healthcare system. Several barriers that hindered the implementation of ASP in Pakistan were identified, including patient- and healthcare system-related barriers.